The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1086/677366
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Levosimendan in Experimental Models of Right Ventricular Hypertrophy and Failure

Abstract: Pulmonary arterial hypertension (PAH) is a fatal disease, and the ultimate cause of death is right ventricular (RV) failure. In this study, we investigated the acute hemodynamic effects of levosimendan in two rat models of RV hypertrophy and failure. Wistar rats were randomized to receive sham surgery (n ¼ 8), pulmonary trunk banding (PTB; n ¼ 8), or monocrotaline injection (MCT; n ¼ 7). RV function was evaluated at baseline and after injection of placebo and two concentrations of levosimendan (12 and 60 μg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
1
20
0
1
Order By: Relevance
“…Levosimendan is currently indicated as an inotrope for acutely decompensated left heart failure patients with low cardiac output . Levosimendan has been shown to acutely improve the failing right heart in monocrotaline models of pulmonary arterial hypertension (PAH) . A variety of preclinical and clinical studies suggest that levosimendan attenuates in pulmonary vascular remodelling and has antiproliferative and anti‐inflammatory effects .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levosimendan is currently indicated as an inotrope for acutely decompensated left heart failure patients with low cardiac output . Levosimendan has been shown to acutely improve the failing right heart in monocrotaline models of pulmonary arterial hypertension (PAH) . A variety of preclinical and clinical studies suggest that levosimendan attenuates in pulmonary vascular remodelling and has antiproliferative and anti‐inflammatory effects .…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data has shown that it possesses beneficial haemodynamic effects and improves right ventriculovascular coupling in patients with PH. Levosimendan has been reported to be a novel calcium‐sensitizing drug and a promising agent for PAH therapy …”
Section: Introductionmentioning
confidence: 99%
“…In some studies, milrinone has been shown to reduce PVR [38]. Data on levosimendan are entirely experimental; however, it has been shown to be more effective than dobutamine for improving ventriculo-arterial coupling in preclinical studies [39,40].…”
Section: Haemodynamic Optimisationmentioning
confidence: 99%
“…En cas d'insuffisance cardiaque aiguë, l'augmentation du débit cardiaque est due à une meilleure fonction ventriculaire gauche mais également à une amélioration de la fonction ventriculaire droite. En effet, sur un modèle murin d'augmentation brutale de la post-charge ventriculaire droite (par cerclage de l'artère pulmonaire ou injection de monocrotaline), le levosimendan a permis une amélioration et une restauration de l'état hémodynamique initial [48]. Ceci est dû à la fois à l'effet inotrope positif mais aussi à la baisse significative des résistances pulmonaires.…”
Section: Insuffisance Cardiaque Aiguëunclassified